2004
DOI: 10.1172/jci22217
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of insulin receptor substrate 2 in β cells and brain causes obesity and diabetes

Abstract: The molecular link between obesity and β cell failure that causes diabetes is difficult to establish. Here we show that a conditional knockout of insulin receptor substrate 2 (Irs2) in mouse pancreas β cells and parts of the brain -including the hypothalamus -increased appetite, lean and fat body mass, linear growth, and insulin resistance that progressed to diabetes. Diabetes resolved when the mice were between 6 and 10 months of age: functional β cells expressing Irs2 repopulated the pancreas, restoring suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 275 publications
(149 citation statements)
references
References 66 publications
9
134
0
6
Order By: Relevance
“…In fact, hypothalamic ARC activity of Gsk3b has been shown to be increased in HF-fed and HF/high-fructose-fed mice (Benzler et al 2012, Anderson et al 2013, whereas overexpression in the mediobasal hypothalamus has been shown to lead to hyperphagia and obesity in mice that were challenged with an HF diet (Benzler et al 2012). The insulin receptor substrate 2 (IRS2) gene, another important modulator of insulin signalling, has been associated with severe human obesity (Lautier et al 2003), whereas the central ablation of Irs2 in mouse models has been shown to lead to obesity (Lin et al 2004, Sadagurski et al 2012. However, a recent study has shown an opposite phenotype, with obesity induced by an HF/high-fructose diet leading to an increase in Irs2 expression (Anderson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hypothalamic ARC activity of Gsk3b has been shown to be increased in HF-fed and HF/high-fructose-fed mice (Benzler et al 2012, Anderson et al 2013, whereas overexpression in the mediobasal hypothalamus has been shown to lead to hyperphagia and obesity in mice that were challenged with an HF diet (Benzler et al 2012). The insulin receptor substrate 2 (IRS2) gene, another important modulator of insulin signalling, has been associated with severe human obesity (Lautier et al 2003), whereas the central ablation of Irs2 in mouse models has been shown to lead to obesity (Lin et al 2004, Sadagurski et al 2012. However, a recent study has shown an opposite phenotype, with obesity induced by an HF/high-fructose diet leading to an increase in Irs2 expression (Anderson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that defects in the action of insulin and leptin in the brain are implicated in the link between obesity and type 2 diabetes (Lin et al 2004;Obici et al 2002;Schwartz and Porte 2005). It is also important to point out that in human dysfunctions alterations in insulin and serotonin efficiency are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in cortical tissue. Insulin signal transduction via the IR and IR substrate 2 has previously been shown to be involved in the regulation of appetite and body mass 35, 42. Concurrent measurements in brain activity, using electroencephalography (EEG), showed that enhanced cerebral insulin signalling with insulin detemir did indeed modulate cortical electrical activity (a significant increase in delta activity was reported).…”
Section: Central Nervous System Hypothesismentioning
confidence: 99%